Teaching now, facing the future. Issue 6 (25th June 2020) - Lu, Xiaoyun; Ding, Yan
Abstract: To obtain knowledge is not the purpose of education, but to develop one's potential ability and to obtain wisdom is. We are living in a fast changing world and knowledge is growing explosively. Therefore, what facts or information students have known in your class is not the most important thing. What really matters is how efficiently students could learn and how those knowledge they have learned can help them to deal with their own tasks in the future. This article introduces our four‐dimensional comprehensive course design and the teaching activities we used to optimize and improve students' learning and developing process.